Evaluating Noninvasive Markers to Identify Advanced Fibrosis by Liver Biopsy in HBV/HIV Co‐infected Adults. Issue 2 (19th August 2019) - Sterling, Richard K.; King, Wendy C.; Wahed, Abdus S.; Kleiner, David E.; Khalili, Mandana; Sulkowski, Mark; Chung, Raymond T.; Jain, Mamta K.; Lisker‐Melman, Mauricio; Wong, David K.; Ghany, Marc G.; ,
Abstract : Noninvasive biomarkers are used increasingly to assess fibrosis in patients with chronic liver disease. We determined the utility of dual cutoffs for noninvasive biomarkers to exclude and confirm advanced fibrosis in hepatitis B virus (HBV)–human immunodeficiency virus (HIV) co‐infected patients receiving combined antiretroviral therapy. Participants were anti‐HIV/hepatitis B surface antigen–positive adults from eight clinical sites in the United States and Canada of the Hepatitis B Research Network. Fibrosis was staged by a central pathology committee using the Ishak fibrosis score (F). Clinical, laboratory, and vibration‐controlled transient elastography (VCTE) data were collected at each site. Dual cutoffs for three noninvasive biomarkers (aspartate aminotransferase‐to‐platelet ratio index, Fibrosis‐4 index [FIB‐4], and liver stiffness by VCTE) with the best accuracy to exclude or confirm advanced fibrosis (F ≥ 3) were determined using established methodology. Of the 139 enrolled participants, 108 with a liver biopsy and having at least one noninvasive biomarker were included: 22% had advanced fibrosis and 54% had normal alanine aminotransferase. The median (interquartile range) of APRI (n = 106), FIB‐4 (n = 106), and VCTE (n = 63) were 0.34 (0.26‐0.56), 1.35 (0.99‐1.89), and 4.9 (3.8‐6.8) kPa, respectively. The area under the curve for advanced fibrosis was 0.69 for APRI, 0.66 for FIB‐4, and 0.87 for VCTE. VCTE cutoffs of 5.0 kPa or less (to exclude) and 8.8 kPa or greater (to confirm) advanced fibrosis had a sensitivity of 92.3% and specificity of 96.0%, respectively, and accounted for 65.1% of participants. Among the 34.9% with values between the cutoffs, 26.1% had advanced fibrosis. Considering APRI or FIB‐4 jointly with VCTE did not improve the discriminatory capacity. Conclusion: VCTE is a better biomarker of advanced fibrosis compared with APRI or FIB‐4 in HBV/HIV co‐infected adults on combined antiretroviral therapy. Using VCTE dual cutoffs, approximately two‐thirds of patients could avoid biopsy to determine advanced fibrosis.